Scientific Diction and Identity Construction in the 2024 Presidential Debate: Implications for Language Learning and Political Discourse - Sari, Lusi Komala; Apakama , Lusi Mgbemgasha (Actual Insight, 2025)
This study investigates the use of scientific diction in the 2024 Indonesian presidential debate as a rhetorical strategy for constructing intellectual identity and power relations. Drawing on critical discourse analysis and a descriptive qualitative approach, the research identifies how scientifically and technically nuanced vocabulary, such as terms related to national security, technology, and policy was employed by presidential candidates to convey credibility, assert authority, and position themselves as knowledgeable leaders. The data were collected from transcriptions of televised debates and analyzed thematically based on diction type, field of reference, and rhetorical function. The findings reveal that scientific diction functions not merely as a communicative device but also as a performative and symbolic resource to enhance public perception, ideological appeal, and discursive power. This phenomenon suggests that language in political contexts is both strategic and ideological. From an educational perspective, these insights contribute to language learning by offering real-world examples for developing critical literacy, academic vocabulary, and rhetorical competence. Scientific diction in political discourse can thus be used as a pedagogical resource to teach persuasive speaking, analytical writing, and discourse awareness in language classrooms.